2020
DOI: 10.18806/tesl.v37i3.1346
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Students’ Willingness to Communicate: Drama-Based Approaches to Language Instruction in English for Academic Purposes Classes

Abstract: A strong willingness to communicate (WTC) in a second language is associated with successful language learning. ESL learners with high levels of WTC will seek opportunities to interact in meaningful communication in English. Engagement in meaningful communication is necessary for language learning as it increases access to comprehensible input, promotes negotiation of meaning, and pushes the learner to produce accurate output. By enhancing instructors’ understanding of factors that impact students’ WTC (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…From a drama perspective, one can argue that successful language learning is linked to a strong desire to communicate in a second language. Lee et al (2020) contend that different levels of E.S.L. learners actively seek opportunities to participate in meaningful English conversations because effective language acquisition hinges on engaging communication.…”
Section: The Role Of Drama In Developing Imagination Among Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a drama perspective, one can argue that successful language learning is linked to a strong desire to communicate in a second language. Lee et al (2020) contend that different levels of E.S.L. learners actively seek opportunities to participate in meaningful English conversations because effective language acquisition hinges on engaging communication.…”
Section: The Role Of Drama In Developing Imagination Among Studentsmentioning
confidence: 99%
“…From a drama perspective, one can argue that successful language learning is linked to a strong desire to communicate in a second language. Lee et al (2020) contend that different levels of ESL students will look for chances to interact and engage in meaningful English communication, simply because language learning requires meaningful communication, which enables students to improve their access to understandable information, encourage meaning negotiation, and force students to generate accurate output.…”
Section: Table 2 Students' Views On the Role Of Drama In Teaching Eng...mentioning
confidence: 99%
“…A recent study by Lee et al (2020) in Canada further indicated drama-based activities can create a safe, relaxing, enjoyable, and motivational learning environment to enhance students' confidence and reduce their anxiety when communicating. Lee et al (2020) noted L2 confidence, anxiety, and motivation are important factors in both L2 learning and students' WTC. If students find the learning process enjoyable and satisfying, then they will be more motivated and more willing to use the language (Dörnyei, 2018).…”
Section: Drama-based Approaches (Dbas) To Improve Students' Willingness To Communicate (Wtc) In Englishmentioning
confidence: 99%